The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1136/jnnp.74.10.1392
|View full text |Cite
|
Sign up to set email alerts
|

Chronic deep brain stimulation for the treatment of tremor in multiple sclerosis: review and case reports

Abstract: Background: Deep brain stimulation (DBS) offers a non-ablative alternative to thalamotomy for the surgical treatment of medically refractory tremor in multiple sclerosis. However, relatively few outcomes have been reported. Objective: To provide a systematic review of the published cases of DBS use in multiple sclerosis and to present four additional patients. Methods: Quantitative and qualitative review of the published reports and description of a case series from one centre. Results: In the majority of repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…Chronic VIM stimulation will produce better results but stimulation parameters probably have to be optimized repeatedly. In some smaller studies and case series, amelioration of tremor could be achieved in 87.7% and of activities of daily life in 76% of operated patients [165]. Simultaneously the level of disability and SF-36 subscales remained largely unchanged (class III evidence [166, 167]).…”
Section: Ataxia and Tremormentioning
confidence: 99%
“…Chronic VIM stimulation will produce better results but stimulation parameters probably have to be optimized repeatedly. In some smaller studies and case series, amelioration of tremor could be achieved in 87.7% and of activities of daily life in 76% of operated patients [165]. Simultaneously the level of disability and SF-36 subscales remained largely unchanged (class III evidence [166, 167]).…”
Section: Ataxia and Tremormentioning
confidence: 99%
“…3,27,29 Over the course of weeks to months, despite continuous thalamic stimulation, tremor is often refractory or recurs. 18,21,62,66 The effectiveness of ventrolateral thalamic DBS in HT remains uncertain due to the limited number of cases, relatively short follow-up, and diverse outcome scales used 1,13,42,50 (Table 1).…”
Section: Prior Surgical Approaches To Htmentioning
confidence: 99%
“…5 Several studies have examined the effects of thalamic DBS on MS tremor (Table 2). [33][34][35][36][37][38] The majority of these were single-center studies with small sample sizes. One study reported unilateral DBS of the Vim in 13 MS patients (11 relapsing progressive; 2 relapsing remitting) after a follow-up of up to 26 months.…”
Section: Multiple Sclerosismentioning
confidence: 99%